Epidemiological concepts and arrhythmogenic mechanisms in patients with atrial fibrillation - Sequeira, Orlando Robert; García, Laura Beatriz; Chávez, Christian Osmar; Falcón, Rocío del Pilar; Meza, Alfredo Javier; Centurión, Osmar (Medicina Clínica y Social, 2025)
Many fundamental aspects of atrial fibrillation (AF) have been little known until a few years ago, and there are several features in AF mechanisms that hinder their proper evaluation. Various external factors induce a slow but progressive process of structural remodeling in the atria. Fibroblast activation, increased connective tissue deposits and fibrosis are the most important elements of this process. The structural remodeling produces an electrical dissociation between the muscle bundles and heterogeneity of the local conduction that favors the phenomenon of reentry and the perpetuation of the arrhythmia. All localized sources of AF, such as ectopic foci, rotors and other stable reentry circuits, cause non-homogeneous and anisotropic conduction away from the source. This conduction is difficult to differentiate from the propagation of multiple waves that the AF maintains, and any of these phenomena can generate rotors detected in intracardiac recordings. The mechanism of focal activity by a source in the pulmonary veins can trigger episodes of AF due to both the triggered activity and the localized reentry mechanism. Patients with a history of AF that in sinus rhythm have an alteration of the P wave morphology and dispersion of the P wave in the ECG have a high susceptibility to develop sustained AF and generally have abnormally prolonged and fractionated atrial electrograms. Additionally, they have a longer P wave duration, and a significantly longer intraauricular and interatrial conduction time of sinus impulses; and a higher incidence of sustained AF induction.
Keywords: Atrial fibrillation; Abnormal Atrial Electrograms; Rotors